FOXM1-AKT Positive Regulation Loop Provides Venetoclax Resistance in AML - Chesnokov, Mikhail S; Borhani, Soheila; Halasi, Marianna; Arbieva, Zarema; Khan, Irum; Gartel, Andrei L. (Frontiers in Oncology, 2021)
Forkhead box protein M1 (FOXM1) is a crucial regulator of cancer development and chemoresistance. It is often overexpressed in acute myeloid leukemia (AML) and is associated with poor survival and reduced efficacy of cytarabine therapy. Molecular mechanisms underlying high FOXM1 expression levels in malignant cells are still unclear. Here we demonstrate that AKT and FOXM1 constitute a positive autoregulatory loop in AML cells that sustains high activity of both pro-oncogenic regulators. Inactivation of either AKT or FOXM1 signaling results in disruption of whole loop and similar transcriptomic changes. AML cells with inhibited AKT activity or stable FOXM1 knockdown display drastic increase in HOXA genes expression that is associated with prominent sensitization to venetoclax treatment. Taken together, our data clearly indicate that AKT and FOXM1 in AML should not be evaluated as single independent regulators but as two parts of a common FOXM1-AKT positive feedback circuit. We also report for the first time a novel FOXM1-dependent mechanism of AML resistance to BCL-2 inhibitor venetoclax. Thus, targeting FOXM1-AKT loop may open new possibilities in overcoming AML drug resistance and improving outcomes for AML patients.